The quality analysis of the national gravimetric network of Lithuania - Petras Petroskevicius; Eimuntas Parseliunas; Rosita Birvydiene; Darius Popovas; Romuald Obuchovski; Lina Papsiene (Geodetski Vestnik, 2014)
The paper reviews the gravimetric measurements carried out in Lithuania over the last twenty years. The first absolute ballistic gravimetric measurements were carried out at the three points by Jaakko Mäkinen (Finish Geodetic Institute) in 1994. The 5 μGal precision of the gravity acceleration was derived. These measurements allowed to adopt the IGSN71 gravity system in Lithuania instead of earlier used Potsdam gravity system. The national first order gravimetric network of Lithuania was developed during the period of 1998–2001. It consists of 51 points. The measurements were carried out by 3–6 LaCoste & Romberg gravimeters. In 2007–2009 the second order gravimetric network was developed. It consists of 635 points. The measurements were carried out by two pairs of the Scintrex CG-5 gravimeters. The gravity acceleration was measured with an accuracy better than 10 μGal.The gravimetric Bouguer anomaly map, based on gravimetric survey of the period 1954–1962, was evaluated against the gravimetric network data. The results of the evaluation show that the accuracy of the gravity acceleration value, derived from the gravimetric map, is about 0.7 mGal and that the average difference between the IGSN71 gravity system and Potsdam gravity system is about 13.93 mGal in Lithuania territory.